Desmopressin Stimulates Parallel Norepinephrine and Tissue Plasminogen Activator Release in Normal Subjects and Patients with Diabetes Mellitus - Grant, M B; Guay, C; Lottenberg, R (Thrombosis and Haemostasis, 1988)
Desmopressin acetate administration markedly stimulates release of tissue plasminogen activator (t-PA) from vascular endothelial cells. The mechanism for this effect is unknown. Because infusion of epinephrine has been shown to increase t-PA levels, we examined the role of endogenous catecholamine mediation of t-PA release by desmopressin. Intravenous desmopressin acetate (0.3 μg/kg) was infused over 30 min in 9 controls and 11 subjects with diabetes mellitus, a condition associated with abnormalities of the fibrinolytic system. Plasma was collected in the supine, overnight fasted state at 15 min intervals (0-60 min) for measurement of t-PA activity, t-PA antigen and fractionated catecholamines. t-PA activity peaked at 30-45 min and subsequently decreased. The norepinephrine levels paralleled the t-PA activity. t-PA activity increased 10-fold from 0.14 ± .12 to 1.49 ± 0.79 IU/ml (Mean ± SD) and plasma norepinephrine increased 2- fold from 426 ± 90 to 780 ± 292 pg/ml. However, epinephrine and dopamine levels did not change significantly. The response to desmopressin of control and diabetic subjects was not shown to differ and their data were combined. We conclude that desmopressin increases plasma norepinephrine in addition to t-PA and that the parallel time course of change suggests a possible role for norepinephrine in mediating endothelial cell t-PA release.
Keywords: Desmopressin; Norepinephrine; Tissue plasminogen activator release (t-PA); Catecholamines; Endothelial cells